Populism and Collective Memory: Comparing Fascist Legacies in Western Europe - Manucci, Luca (2020)
Right-wing populism is a global phenomenon that challenges several pillars of liberal democracy, and it is often described as a dangerous political ideology because it resonates with the fascist idea of power in terms of anti-pluralism and lack of minorities’ protection. In Western Europe, many political actors are exploiting the fears and insecurities linked to globalization, economic crisis, and mass migrations to attract voters. However, while right-wing populist discourses are mainstream in certain countries, they are almost completely taboo in others. Why is right-wing populism so successful in Italy, Austria, and France while in Germany it is marginal and socially unacceptable? It is because each country developed a certain collective memory of the fascist past, which stigmatizes that past to different levels. For this reason, right-wing populism can find favorable conditions to thrive in certain countries, while in others it is considered as an illegitimate and dangerous idea of power. Through a comparative study of eight European countries, this book shows that short-term factors linked to levels of corruption, economic situation, and quality of democracy interact with long-term cultural elements and collective memories in determining the social acceptability of right-wing populist discourses.